Sosialisasi Pentingnya Menjaga Kebersihan Lingkungan Pantai Kepada Masyarakat Pesisir Guna Menjaga Kelestarian Ekosistem Pantai Payangan - Afni Nur Rosyidah; Inge Wiliandani Setya Putri; Arik Aguk Wardoyo; Hilda Eka Ningtyas; Faiqotul Munawaroh (Edujavare Publishing, 2024)
Maintaining a clean environment is of course very important, especially for people who live in areas around the beach. However, several beaches in Jember still tend to be littered with rubbish, thus disrupting the sustainability of the coastal ecosystem. This research aims to provide outreach about the importance of keeping the coastal environment clean so that coastal communities can maintain the sustainability of coastal ecosystems through waste management education. In this case, it is outreach to the community around Payangan beach. This service method is the PAR (Participatory Action Research) service method. The data collection technique uses a qualitative approach technique which includes surveys, interviews, and documentation analysis. The research results show that outreach involving the active participation of the community, stakeholders and local government has had a positive impact in increasing awareness of the importance of keeping beaches clean. This outreach includes correct waste management including reduction, recycling, and safe disposal. It was concluded that there is a need for continued support from the government and non-governmental organizations to implement broader and more sustainable outreach programs to preserve coastal ecosystems in the future.